Effects of Squash (Cucurbita maxima) Meal on Growth and Performance in Broiler Chicken Diets - Fernandez, Marianne; Vergara, Julius (Journal of Interdisciplinary Perspectives, 2025)
This study examines the potential benefits of incorporating squash (Cucurbita maxima) meal into broiler chicken diets to enhance growth performance and feed conversion efficiency. Using a randomized complete block design, the research evaluated four different treatments: a control diet with 100% formulated feed, and three experimental diets with 5%, 10%, and 15% squash meal (SM) inclusion. Over a 20-day feeding period, various metrics were assessed, including initial weight, final weight, weight gain, feed consumption, and feed conversion efficiency (FCE). The findings revealed that higher levels of squash meal supplementation, particularly at 15% inclusion, significantly increased final weight, weight gain, and feed conversion efficiency. Notably, feed consumption remained consistent across all treatments. The research highlights the promising potential of squash meal, especially at a 15% inclusion rate, as an effective dietary supplement for promoting broiler growth. However, further studies are needed to explore the optimal balance between growth enhancement and feed consumption.